Semi-structured Interview of Moral cognitionS (SIMS) - O'REILLY, KENNETH; KENNEDY, HARRY (Trinity College Dublin, School of Medicine, Department of Psychiatry, 2018)
This ‘Semi-structured Interview of Moral cognitionS’ (SIMS) is a synthesis of our experience and research in the fields of clinical/forensic psychology and forensic psychiatry. As an interview the SIMS aims to make the non-understandable understandable and to demystify serious acts of violence. The ‘Semi-structured Interview of Moral cognitionS’ assesses six broad domains which may be associated with violence (O’Reilly et al, 2017; Graham and Haidt, 2012). Five of the domains concern the moral themes of ‘Care-Harm,’ ‘Fairness-injustice’, ‘Loyalty-Betrayal’, ‘Authority’, and ‘Purity’, which are drawn from moral foundations theory (Haidt, 2007), in contrast the sixth domain focuses on ‘Egoism and immorality’. The five moral domains are thought to be innate and universal appearing in all cultures (Haidt, 2007). But cultures and individuals may differ with regard to how specific acts are categorised allowing for considerable variation (Haidt, 2007). Moral foundations theory and moral psychology more generally provides a framework for understanding what individuals believe to be moral, however mistaken they may be, and therefore can be contrasted with moral philosophy where the task is often to define what is moral (Pinker, 2002). Because moral psychology concerns what individuals believe, moral attitudes can be erroneously used to justify violence (Fisk and Rai, 2014; Pinker, 2002; O’Reilly et al, 2018 in press). Mercy killings, feuds, crimes of passion, punishments, and honour killings can all be associated with specific moral domains (Fisk and Rai, 2014; Graham and Haidt, 2012)
Keywords: Forensic Psychiatry; Forensic Psychology; Forensic Psychology; forensic psychiatry